The impact of the crisis on the remuneration in the public sector - de Luxán Meléndez, José María (Cuadernos de Gobierno y Administración Pública, 2017)
This work analyses the evolution of wage costs in the Spanish public administration. It presents some characteristics of the public employment, which are related to the orientation of the remuneration policy. The cost and evolution of the Spanish policy is compared to its European counterparts. In the discussion it is stressed that the Spanish administration is small and relatively expensive, that it might have lost its innovative capacity and that it has a rigid and centralized retributions system. This article presents three lines of change: Increase employment and stabilize expenditure, innovative growth and assurance of sustainable professional trajectories and finally improve institutionalization of participative budgets and boost collective bargaining.